Immersion as Fiction: Divergent Uses of Emotion in Artistic and Occupational Virtual Reality (Itinera, 2025)
This paper investigates the relationship between immersion, emotion, and imagination in virtual reality (VR), focusing on two seemingly distant domains: Alejandro G. Iñárritu’s installation Carne y Arena (2017) and VR-based workplace safety training. Both cases demonstrate that simulated environments can elicit authentic emotional responses – such as fear, stress, or vulnerability – yet the implications of these experiences diverge sharply. Drawing on theories of presence and the “paradox of fiction”, we argue that VR should be understood not as a substitute for imagination but as a heightened form of fiction that depends on the user’s willingness to engage in make-believe. While Carne y Arena frames affect as an entry point for moral imagination within an explicit artistic and symbolic context, occupational safety training instrumentalizes emotion as a means of behavioral conditioning within a productivist framework. The danger in both domains lies not in immersive experience itself but in mistaking a single simulation for the fullness of lived reality.